A Slotted Planar Antenna for 5G Applications (ELEKTRIKA- Journal of Electrical Engineering, 2022)
This paper presents a slotted planar microstrip patch antenna for the 5th generation communication. The planar microstrip patch antenna is designed with a square patch and two longitude slots at 3.5 GHz, using FR4 substrate and feds by a coplanar waveguide structure (CPW). The proposed antenna was simulated, analysed, and optimized using computer simulation technology (CST) software. Simulation results show a good return loss of greater than10 dB and impedance bandwidth of about 650MHz, which meet the requirements of future 5G applications. In this work, the geometry of the presented antenna and its related parameters are presented and discussed